Who are we Trying to Protect? The Role of Vulnerability Analysis in New Zealand's Law of Negligence - Fletcher, Scott William Hugh (Victoria University of Wellington Law Review, 2016)
New Zealand has incorporated ideas of vulnerability within its law of negligence for some years. It has not, however, clarified what is meant by vulnerability or the role the concept plays within the broader duty of care framework. Several obiter comments in Body Corporate No 207624 v North Shore City Council (Spencer on Byron) suggest the concept ought not to be part of the law due to its uncertain and confusing nature. Subsequent cases have, however, continued to use the concept, and continue to use it despite both its historically ill-defined nature and the additional uncertainty added by Spencer on Byron. This article argues that vulnerability can and ought to be a part of New Zealand negligence law. With a consistent application of a single test for vulnerability – that established in the High Court of Australia in Woolcock Street Investments Pty Ltd v CDG Pty Ltd – vulnerability can be conceptually certain and provide useful insight into the issues posed by the law of negligence.